The Thematic Content Short Course Model for Accelerating Language Proficiency Among Learners of German and Mandarin Language and Literature: An Experimental Study - Aini, Desti Nur; Kharis, M; Jayanti, Cicik Tri; Amalia, Raida Zharfa (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Language learning, particularly foreign languages, is not always appealing or effective for the general public, especially when the available time is limited and expectations include both engagement and practical competency tailored to specific needs. This study aims to produce a viable instructional module to introduce foreign languages, specifically German and Mandarin, to the general public in the form of a short course. This research falls into the research and development category, with effectiveness determined not only through expert validation but also by measuring its impact via a pre-test and post-test experimental design. A total of 10 beginner learners participated in the short course. Data were analyzed using content analysis, examining qualitative data gathered from learner feedback, comments, and suggestions on the short course to identify themes and patterns that could inform the development of the short course model. The results indicate that the developed short course model of the themes ‘sich vorstellen’ (perkenalan), ‘Familie’ (Keluarga), ‘Alltagsleben’ (kehidupan sehari-hari), ‘Essen und Trinken’ (makanan dan minuman), and ‘Das Hobby’ (hobi) can significantly enhance learner competency. The most effective components in boosting learner competency were practical training, group discussions, and feedback. Furthermore, the findings demonstrate that the developed short course model increases learners’ motivation and self-confidence.